Persepsi Siswa SLTA di Kabupaten Tanah Datar tentang Jurusan Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam IAIN Batusangkar - Widi Nopiardo (ZAWA: Management of Zakat and Waqf Journal, 2022)
Perception is an integral part in influencing interest. Students' perceptions of new majors such as the Department of Zakat and Waqf Management need to be investigated as consideration for related parties. This research is a field research with a quantitative approach. The results showed that in relation to the percentage index of the perception variable items, the average percentage index obtained was 78.10. Thus, it can be interpreted that the percentage score interval is good, because it is in the 60-79.99% interval. This shows that respondents have a good perception of the Department of Zakat and Waqf Management. Meanwhile, from open questions given to respondents, data obtained that 95 people or 95.96% have a good perception, 3 people or 3.03% are quite good, with various comments about the Department of Zakat and Waqf Management Department FEBI IAIN Batusangkar, while 1 people or 1.01% do not know.